CEBPB is associated with active tumor immune environment and favorable prognosis of metastatic skin cutaneous melanoma - Yang, Jingrun; Xu, Yang; Xie, Kuixia; Gao, Ling; Zhong, Wenying; Liu, Xinhua (Frontiers in Immunology, 2022)
Metastatic skin cutaneous melanoma (SKCM) is a common malignancy which accounts for low morbidity but high mortality of skin cancer. SKCM is characterized by high lymphocyte infiltration, whereas, the states of infiltrated cells are variable across patients which result in heterogeneous prognosis and impede the appropriate clinical decision. So, identification of markers associated with lymphocyte infiltration, cell states and prognosis of SKCM is urgently needed. In this study, we report that CEBPB, a transcriptional factor, is mainly expressed in macrophages in metastatic SKCM and associated with active tumor immune environment and favorable prognosis through integrated analysis of single cell and bulk RNA-seq datasets. High CEBPB expression is significantly associated with active inflammation and immune response pathways in both macrophages and bulk SKCM tumor tissues. A signature based on CEBPB-associated genes that are specifically expressed in macrophage could robustly separate prognostically different metastatic SKCM patients. What’s more, associations between the signature and tumor microenvironment of metastatic SKCM with respect to T cell recruitment and state, inflammation response, angiogenesis and so on were also determined. In conclusion, we here present the first report about CEBPB in tumor immune environment and prognosis regulation in metastatic SKCM and construct a reliable signature, which should provide a useful biomarker for patient prognosis stratification and therapeutic selection.